2018
DOI: 10.12659/msm.910794
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Patients’ Stigma and Self-Efficacy on Relationships Between Doctors’ Empathy Abilities and Patients’ Cellular Immunity in Male Breast Cancer Patients

Abstract: BackgroundDoctors’ empathy is closely related to patients’ health. This study aimed to examine whether patients’ stigma and self-efficacy play a mediating role in the relationship between doctors’ empathy abilities and patients’ cellular immunity in male patients with breast cancer.Material/MethodsDoctors’ empathy scores and patients’ demographic data, disease condition, stigma, and self-efficacy were measured. Patient T cell subset was tested at admission and 3 months after the operation and was compared by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
2
3
0
2
Order By: Relevance
“…Thompson et al proved that empathy improved patient-centered care quality and the outcome of heart disease patients [39]. In our previous studies, we also confirmed the function of empathy ability of physicians and nurses on mental health indexes and immunological functioning in breast cancer, prostate cancer, and lung cancer patients [4042]. These results reveal that medical personnel need to improve their empathy ability.…”
Section: Discussionsupporting
confidence: 84%
“…Thompson et al proved that empathy improved patient-centered care quality and the outcome of heart disease patients [39]. In our previous studies, we also confirmed the function of empathy ability of physicians and nurses on mental health indexes and immunological functioning in breast cancer, prostate cancer, and lung cancer patients [4042]. These results reveal that medical personnel need to improve their empathy ability.…”
Section: Discussionsupporting
confidence: 84%
“…Our results indicate that while oncologists may be increasingly aware of MBC, patients and clerical staff at breast health centers are not necessarily as widely informed or welcoming of male and masculine‐presenting patients. The clinical environment plays a critical role in shaping MBC's feelings of exclusion and shame around the time of diagnosis . This suggests an urgent need to increase awareness of MBC and masculine‐presenting patients, including trans and non‐binary patients, in these spaces .…”
supporting
confidence: 90%
“… 12 The scale measured dimensions of internalized shame and has been used previously to measure stigma in the context of lung cancer, 13 as well as other cancer and patient-provider communication settings. 14 16 Participants indicated the degree they endorsed the following items: “I feel others think I am to blame for my illness;” “I do not feel I can be open with others about my illness;” “I fear someone telling others about my illness without my permission;” “I feel I need to keep my illness a secret;” “I feel I am at least partially to blame for my illness.” Participant scores were retained if they answered any 4 of the 5 items, with the missing fifth item mean-imputed.…”
Section: Methodsmentioning
confidence: 99%